2021
DOI: 10.3390/horticulturae7080215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Runner Removal and Partial Defoliation on the Growth and Yield Performance of ‘Favori’ Everbearing Strawberry Plants

Abstract: It is not known to what degree growth and fruit yield are source-limited in everbearing strawberry plants. The growth and yield performance effect of bi-weekly removal of all runners and/or one or two leaves during the cropping season of tunnel-grown ‘Favori’ everbearing strawberry plants was determined. Plants were grown on a table-top system in an open plastic tunnel under natural light conditions in Norway from May to October. Removal of runners and leaves was bi-weekly from 5 June until 25 September. Fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
4
13
2
Order By: Relevance
“…Runners in both cultivars were formed after 8 weeks (Figure 1C) of SD treatment, irrespective of the temperature. This is consistent with earlier research, where the runner capacity of EB has been shown to be low and cultivar dependent [13,44].…”
Section: Temperature and Photoperiod Effect Plant Growth And Developmentsupporting
confidence: 93%
See 2 more Smart Citations
“…Runners in both cultivars were formed after 8 weeks (Figure 1C) of SD treatment, irrespective of the temperature. This is consistent with earlier research, where the runner capacity of EB has been shown to be low and cultivar dependent [13,44].…”
Section: Temperature and Photoperiod Effect Plant Growth And Developmentsupporting
confidence: 93%
“…This is supported by previous studies, where EB produced more flowers in LD than in SD [13,20]. However, a more frequent flower mapping approach, to follow the fate of the meristems across a wider range of temporal changes, would help deduce precise conclusions [24][25][26][27]30,44]. In addition, complex phenological modelling, such as done by Labadie et al (2019), would be required to help dissect these changes, reasoning and their effects on the overall yield [43].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Important reasons for the differences are the small plants and the relative short experimental periods that deliberately were used for both plant types in the phytotron in order to study growth control during the vegetative plant state. Because of this, and since flowers and developing fruits are strong sinks for photosynthates in EB strawberry (Sønsteby et al 2021), the differences between SF and EB types would probably have been more distinct if longer experimental periods had been used so that generative development would have represented a greater part of the experimental period. Hunt (1990) also concluded that the RGR decreases as plants become larger due to their increased anatomical and morphological differentiation and larger translocatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A serious shortcoming of the European production system is, however, that it does not produce a continuous and stable supply of ripe berries during the harvest season, but rather a series of flowering and fruiting flushes separated by gaps with little or no production [4][5][6][7]. The first, and usually largest, fruit flush, which originates from inflorescences produced during plant raising in the previous year [7], is usually followed by an off period of 2-3 or more weeks with little fruit. This causes discontinuous fruit supply and reduced total yields and represents a big challenge in commercial production.…”
Section: Introductionmentioning
confidence: 99%